Communicating with the World of Beings : The World Heritage rock art sites in Alta, Arctic Norway - Helskog, Knut Arne (Oxbow Books, 2014)
Cover -- Copyright Page -- Title Page -- Contents -- Foreword -- Introduction -- The World of Beings -- The Natural Surroundings -- Age -- Making Rock Art -- Period I -- Period II -- Human Figures -- Reindeer -- Elk -- Bear -- Other Land Animals and Birds -- Fish and sea mammals -- Boats -- Equipment -- Abstract Figures -- Summary -- Period III -- Human Figures -- Reindeer -- Elk -- Bear -- Birds -- Fish and sea mammals -- Boats -- Equipment -- Abstract Figures -- Summary -- Period IV -- Human Figures -- Reindeer -- Other members of the deer family -- Bear -- Other animals and fish -- Abstract Figures -- Summary -- Period V -- Human Figures -- Reindeer and Elk -- Other animals -- Boats -- Summary -- Period VI -- Summary -- Paintings -- A Northern Fennoscandian Perspective -- Final Phase of Rock Art -- World Cultural Heritage in Alta -- References.